‘Delusional’ obsessive compulsive disorder responding to behaviour therapy: a case report - Hanwella, Raveen; Perera, R. (Sri Lanka Journal of Psychiatry, 2011)
A 35 year old female with severe obsessive thoughts and compulsions of more than 10 years duration was referred for therapy. The obsessions consisted of thoughts that sharp objects embedded in her clothing and other items of use would enter her body and circulation. The compulsions consisted of extreme precautions taken to avoid contact with sharp objects. These were compounded by the near delusional belief that people around her were conspiring to place sharp objects near her. Though there was some initial pessimism she responded well to exposure and response prevention combined with medication.
Keywords: OCD; behaviour therapy; delusional